Computational fluid dynamic simulation of a sorption-enhanced palladium membrane reactor for enhancing hydrogen production from methane steam reforming. (15th March 2018) - Ji, Guozhao; Zhao, Ming; Wang, Geoff
Abstract: To understand the reaction process of methane steam reforming in a sorption enhanced membrane reactor (SEMR), a computational fluid dynamic (CFD) model was developed to simulate the methane (CH4 ) steam reforming in a palladium-based membrane reactor using a Ni-based catalyst and Na2 ZrO3 CO2 sorbent. The CFD model gained the insight of details in the reactor which could not be obtained by experiment. With the detailed information, this model detected the difference of reaction kinetics and fluid dynamic conditions in a SEMR and a traditional membrane reactor (MR). The comparison suggests that sorption-enhanced membrane reactor not only decreases CO2 fraction, but also improves hydrogen (H2 ) production by increasing reaction rates, CH4 conversion and H2 yield. The poisoning effect of carbon monoxide (CO) on the palladium membrane can also be minimized by reduced CO fraction as a result of in-situ CO2 capture. Highlights: Sorption enhanced membrane reactor was proposed to enhance H2 yield. H2 permeation and CO2 capture interacted with methane steam reforming. Validated CFD model assessed the enhancements of methane steam reforming. Na2 ZrO3 sorbents significantly increased the H2 yield and CH4 conversion. CO poisoning to palladium membrane was also minimized by CO2 removal.